Students’ Perspective on the Implementation of Gagne’s Nine Instructional Events in Collaborative Project-Based English Language Teaching - Yulinda, Desi; Yundayani, Audi; Juhana, Juhana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research is a qualitative study that aims to describe students' perspectives on the implementation of Gagne's Nine Events of Instruction in the process of project-based collaborative learning in English subject at one of the high schools in Batam. The informants of this study were 132 students from three classes of grade XI. The data collection methods used were questionnaires and interviews with 6 students randomly selected based on their academic performance from the same classes. The data were analyzed using thematic analysis. The result of this study showed that the students responded positively to the implementation of Gagne's Nine Events of Instructions in project-based collaborative learning in the learning process. Gagne's framework has been successful in improving students' understanding, fostering, and becoming a platform for creativity development, and creating a pleasant learning atmosphere for teachers and students. They also agreed that Gagne's Nine Events of Instructions in project-based collaborative learning has an impact on building students' positive character personally and socially.